All Roads Lead to Serfdom Confronting Liberalism's Fatal Flaw. - Aubrey, Thomas (Bristol University Press, 2022)
Drawing on the German ordoliberal tradition, this book argues that liberalism's reliance on a utilitarian policy framework has resulted in increased concentrations of power, restricting freedom and equality. It proposes an alternative public policy framework and offers a practical pathway to realign policy making with liberal ideas.